2023
DOI: 10.1039/d2md00415a
|View full text |Cite
|
Sign up to set email alerts
|

Oxazolidinones as versatile scaffolds in medicinal chemistry

Abstract: Oxazolidinone is a five-membered heterocyclic ring which find broad biological applications in medicinal chemistry. Among the three possible isomers, 2-oxazolidinone is the most investigated ring in drug discovery. Linezolid was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 175 publications
0
9
0
Order By: Relevance
“…Although 2oxazolidinone has traditionally been known as a pharmacophore with antibacterial effect, [62] recent studies revealed its high anticancer potential. [63][64][65][66][67] Phthalimide 6 b and uracil 6 e derivatives displayed slightly increased antiproliferative activity in M-HeLa cells with IC 50 values of 24.5 (SI = 2.52) and 21.6 μM (SI = 3.31) respectively (Table 3, Figure 5). Compound 6 e was also found to be selective against MCF-7 cells (SI = 2.75, Figure 5), albeit with a higher IC 50 value (26.0 μM) compared to 1 and 2 (Table 3).…”
Section: In Vitro Cytotoxic Activity Of Michael Adducts Of Arglabin A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although 2oxazolidinone has traditionally been known as a pharmacophore with antibacterial effect, [62] recent studies revealed its high anticancer potential. [63][64][65][66][67] Phthalimide 6 b and uracil 6 e derivatives displayed slightly increased antiproliferative activity in M-HeLa cells with IC 50 values of 24.5 (SI = 2.52) and 21.6 μM (SI = 3.31) respectively (Table 3, Figure 5). Compound 6 e was also found to be selective against MCF-7 cells (SI = 2.75, Figure 5), albeit with a higher IC 50 value (26.0 μM) compared to 1 and 2 (Table 3).…”
Section: In Vitro Cytotoxic Activity Of Michael Adducts Of Arglabin A...mentioning
confidence: 99%
“…Of special interest is the high selectivity index (SI) for compound 6 c against duodenum adenocarcinoma HuTu 80 versus normal Chang liver cells (SI=5.45, Figure 5). Although 2‐oxazolidinone has traditionally been known as a pharmacophore with antibacterial effect, [62] recent studies revealed its high anticancer potential [63–67] . Phthalimide 6 b and uracil 6 e derivatives displayed slightly increased antiproliferative activity in M‐HeLa cells with IC 50 values of 24.5 (SI=2.52) and 21.6 μM (SI=3.31) respectively (Table 3, Figure 5).…”
Section: In Vitro Cytotoxic Activity Of Michael Adducts Of Arglabin A...mentioning
confidence: 99%
“…The efficiency and selectivity of multicomponent reactions in which three or more substrates are streamlined towards the formation of a single product enable the development of novel synthetic strategies. [1] In particular, the Cu(I)-catalyzed four-component coupling of amines, aldehydes, alkynes and CO 2 is a versatile and attractive method for the synthesis of oxazolidinones, a class of heterocyclic scaffold exhibiting applications in medicinal chemistry (novel antibiotics against microbial resistance, antitubercular activity, antiviral and anti-cancer agents via topoisomerase II inhibition), [2] molecular chemistry (chiral auxiliaries in enantioselective catalysis) [3] and materials science (polymeric biocidal films, flame retardants), [4] due to their unique structural and hydrogen bonding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Lactams and other nitrogen-containing heterocyclic compounds such as imidazolidinones, oxazolidinones, and imides are important structural units in a large number of natural products and pharmaceuticals. 1–4 In recent years, the selectivity and reactivity of these nitrogen-containing heterocycles as hydrogen atom donors (H-donor), XH, in hydrogen atom transfer reactions (HAT, X–H + Y → X + Y–H) have attracted significant attention from a large number of researchers, gradually becoming a research hotspot. 5–12 Accordingly, it is necessary to develop methods to evaluate the H-donating ability of these nitrogen-containing heterocyclic compounds as H-donors using their characteristic physical parameters.…”
Section: Introductionmentioning
confidence: 99%